2010
DOI: 10.1016/j.rbmo.2009.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Modified natural cycle IVF and mild IVF: a 10 year Swedish experience

Abstract: Modified natural cycle IVF (mnc-IVF) or mild IVF (m-IVF) was offered to selected patients between 1996 and 2007; 43 patients during 129 cycles were treated with mnc-IVF and 145 couples during 250 cycles were treated with m-IVF. Comparison with outcome from conventional IVF cycles during the same time period and in the same clinic was performed. Although 53.5 and 39.6% of started cycles respectively never reached embryo transfer, the ongoing pregnancy rates per embryo transfer were 26.7% for mnc-IVF and 27.2% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 17 publications
(18 reference statements)
1
33
0
Order By: Relevance
“…Initially our patients with autotransplanted tissue were treated as all other patients in our clinic suspected to be low responders with a long GnRH agonist protocol and subsequent stimulation with high doses of recombinant FSH, but because this yielded only a very modest number of oocytes of 1.3 per cycle, we changed our policy and began to treat these women with a modified natural cycle IVF with the aim to use the single follicle that spontaneously develops, in accordance with the experience obtained in other clinics (29,(31)(32)(33). We achieved a total of three clinical pregnancies after IVF giving an implantation rate of 5% per cycle, which is very low, but 33% per ET, which is comparable to, or even better than, results obtained by others, who treated low-responder patients in a modified natural cycle (31)(32)(33)(34)(35)(36)(37)(38). Forty-one of the 49 oocytes retrieved in our group derived from the ovary, which seems to be the site most suited for grafting.…”
Section: Transplantation Of Ovarian Tissue In 12 Womensupporting
confidence: 82%
“…Initially our patients with autotransplanted tissue were treated as all other patients in our clinic suspected to be low responders with a long GnRH agonist protocol and subsequent stimulation with high doses of recombinant FSH, but because this yielded only a very modest number of oocytes of 1.3 per cycle, we changed our policy and began to treat these women with a modified natural cycle IVF with the aim to use the single follicle that spontaneously develops, in accordance with the experience obtained in other clinics (29,(31)(32)(33). We achieved a total of three clinical pregnancies after IVF giving an implantation rate of 5% per cycle, which is very low, but 33% per ET, which is comparable to, or even better than, results obtained by others, who treated low-responder patients in a modified natural cycle (31)(32)(33)(34)(35)(36)(37)(38). Forty-one of the 49 oocytes retrieved in our group derived from the ovary, which seems to be the site most suited for grafting.…”
Section: Transplantation Of Ovarian Tissue In 12 Womensupporting
confidence: 82%
“…A recent study showed that a supraphysiological maternal estradiol environment was correlated with an increased risk of low birth weight and smallfor-gestational age neonates [23]. Moreover, many studies have shown that the developmental potential of oocytes obtained from natural cycles is better than those from COH cycles [24,25]. However, the underlying molecular mechanisms remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, unstimulated cycles or COH with a low stimulation dose are increasingly being recommended by reproductive specialists. Natural cycles and mild stimulation cycles are cost-effective and show a low risk of complications such as ovarian hyperstimulation syndrome,while the pregnancy rates per embryo transfer remain acceptable [24]. Especially, mild protocol has been proven to obtain a comparable IVF outcome as long protocol for patients with expected poor ovarian response [46].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, we interpreted these findings to suggest that follicle quality is more important than follicle quantity in influencing the probability of pregnancy in patients undergoing IVF/ICSI. The concept of follicle quality versus quantity in assisted reproduction is supported by the increasing body of evidence to promote the use of natural cycle IVF and minimal stimulation protocols, especially in patients with a previous poor response or hyperstimulation (24)(25)(26). Mild stimulation results in a reduction in the number of follicles that develop and embryos retrieved, but a lower embryo aneuploidy rate and comparable implantation rate (27,28).…”
Section: Discussionmentioning
confidence: 99%